Una aproximación a los retos para la implementación de la inteligencia artificial en el proceso de certificación ambiental - Barrenechea Sangama, Jaquelin (Pontificia Universidad Católica del Perú, 2025)
The implementation of reliable artificial intelligence in the environmental certification process requires overcoming traditional challenges, such as limited internal and inter-institutional coordination, the absence of a systemized and updated environmental database, the obsolete and differentiated IT and digital infrastructure in entities with environmental competence, as well as the dispersed and imprecise regulation on the subject. This would make it possible to simplify administrative procedures, optimize times, standardize criteria, streamline accompanying actions, achieve effective citizen participation and improve technical-legal actions in environmental assessment.

La implementación de una inteligencia artificial confiable en el proceso de certificación ambiental requiere superar retos tradicionales, tales como, la limitada coordinación interna e interinstitucional, la ausencia de una base de datos ambiental sistematizada y actualizada, la obsoleta y diferenciada infraestructura informática y digital en las entidades con competencia ambiental, así como, la dispersa e imprecisa regulación en la materia. Esto permitiría simplificar los procedimientos administrativos, optimizar los tiempos, uniformizar los criterios, agilizar las acciones de acompañamiento, alcanzar una participación ciudadana efectiva y mejorar las actuaciones técnico-legales en la evaluación ambiental.
An approach to the challenges for the implementation of artificial intelligence in the environmental certification process
Keywords: Environmental Certification; Environmental Assessment; Artificial Intelligence; Digital Transformation; Institutional Coordination; Database; Administrative Law; Peru; Certificación Ambiental; Evaluación Ambiental; Inteligencia Artificial; Transformación Digital; Coordinación Institucional; Base de Datos; Derecho Administrativo; Perú; https://purl.org/pe-repo/ocde/ford#5.05.00